Acceptance or rejection of vaccination against influenza and SARS-CoV2 viruses among primary care professionals in Central Catalonia. A cross-sectional study - Aïna Fuster-Casanovas; Josep Vidal-Alaball; Anna Bonet-Esteve; Raquel Muñoz-Miralles; Queralt Miró Catalina (Vaccine: X, 2023)
Background: With the outbreak of the SARS-CoV-2 pandemic, the uncertainty about the real impact of coinfection with other viruses, and the increased risk of mortality in the case of coinfection with the influenza virus, health authorities recommended an increase in influenza vaccination coverage among at-risk groups to minimize the possible impact on individuals and the healthcare system. Recommendations for influenza vaccination during the 2020–2021 campaign in Catalonia were focused on increasing vaccination coverage, especially for social and healthcare workers, elderly people and at-risk individuals of any age. The objectives for the 2020–2021 season in Catalonia were to reach 75 % for the elderly and for social and healthcare workers, and 60 % for pregnant women and at-risk groups. In the case of healthcare professionals and those over 65 years of age, the target was not met. Vaccination coverage reached 65.58 % and 66.44 %, respectively (in the 2019–2020 campaign it was 39.08 %).Analysing and following up on the background and context in which health professionals accept influenza vaccination will help develop strategies for long-term influenza vaccination campaigns. The present study looks at healthcare professionals in a specific territory where the reasons for acceptance or refusal of the influenza vaccine during the 2021–2022 vaccination campaign, as well as the reasons for acceptance or refusal of the COVID-19 vaccine, were analysed by means of an online survey. Methods: Calculations suggested that a random sample of 290 individuals would be sufficient to estimate, with 95% confidence and a precision of +/- 5 percentage units, a population percentage that was expected to be around 30%. The required replacement rate was 10%.The R statistical software (version 3.6.3) was used for the statistical analysis. Confidence intervals were 95 % and contrasts with a p-value of < 0.05 were considered significant. Findings: Of the 1921 professionals to whom the survey was sent, 586 (30.5%) responded to all the questions. 95.2% of respondents were vaccinated against COVID-19 and 66.2% against influenza.It was observed that the relationship between sociodemographic characteristics and the decision to get vaccinated was different for influenza and COVID-19. The reasons for accepting the COVID-19 vaccine with the highest percentage were firstly protecting family (82.2%), self-protection (74.9%) and also protecting patients (57.8%). Otherwise, other reasons not described in the survey (50%) and mistrust (42.3%) were the reasons for rejecting the COVID-19 vaccine.Regarding influenza, the most relevant reasons for which professionals got vaccinated were self-protection (70.7%), protecting family (69.7%) and protecting patients (58.4%). Reasons for refusing the influenza vaccine were reasons not mentioned in the survey (29.1%) and the low probability of suffering complications (27.4%). Interpretation: Analysing the context, territory, sector, and the reasons for both accepting and refusing a vaccine will help develop effective strategies. Although vaccination coverage against COVID-19 was very high throughout Spain, a marked increase in influenza vaccination in the context of COVID-19 was observed among healthcare professionals in the Central Catalonia region compared to the previous pre-pandemic campaign.